Not all (N)SAID and done: Effects of nonsteroidal anti‐inflammatory drugs and paracetamol intake on platelets - Ben Driver; Denese C. Marks; Dianne E. van derWal (Research and Practice in Thrombosis and Haemostasis, 2020)
Abstract Platelets are key mediators of hemostasis and thrombosis and can be inhibited by nonsteroidal anti‐inflammatory drugs (NSAIDs). As a result, platelet donors are temporarily deferred from donating if they have recently taken NSAIDs such as aspirin or ibuprofen. Despite these measures, a proportion of platelet donations show exposure to these drugs; however, little is known about the effect of NSAIDs and their metabolites on platelet quality in vivo and during storage. In this review, the effect of NSAIDs on platelet function is summarized, with a focus on the widely consumed over‐the‐counter (OTC) medications aspirin, ibuprofen, and the non‐NSAID paracetamol. Aspirin and ibuprofen have well‐defined antiplatelet effects. In comparison, studies regarding the effect of paracetamol on platelets report variable findings. The timing and order of NSAID intake is important, as concurrent NSAID use can inhibit or potentiate platelet activation depending on the drug taken. NSAID deferral periods and maximum platelet shelf‐life is set by each country and are revised regularly. Reduced donor deferral periods and longer platelet storage times may affect the quality of platelet products, and it is therefore important to identify the possible impact of NSAID intake on platelet quality before and after storage.